Pengaruh penempatan terhadap kinerja pegawai melalui komitmen organisasional di Pondok Pesantren - Mastur Mastur (Jurnal Integrasi Sumber Daya Manusia, 2023)
Islamic boarding schools as educational institutions that are very much needed by the community need to be maintained for their sustainability. The sustainability of the pesantren is determined by how well the existing employees are able to perform. This article examines how to improve performance in Islamic boarding schools, resulting in improved employee performance. Using PLS analysis software with saturated sampling method. Forging employees has a positive and insignificant effect on performance, meaning that the placement process must be adjusted to the competence of employees, so that it will give birth to good performance. Employee placement has a positive and significant effect on organizational commitment, this means that the placement will increase organizational commitment. Organizational commitment has a positive and significant effect on employee performance, the existence of organizational commitment will result in increased employee performance. Organizational commitment is capable of mediating between the placement of employees on employee performance, the placement will give birth to organizational commitment and will have implications for increasing employee performance.